The restoration of creation in the early Anglo-Saxon vitae of Cuthbert and Guthlac - Brooks, B (2016)
This thesis explores the relationship between Creation and the saints Cuthbert and Guthlac in their Anglo-Latin and Old English vitae. It argues that this relationship is best understood through received theological exegesis concerning Creation's present state in the postlapsarian world. The exegesis has its foundation in Augustine’s interpretations of the Genesis narrative, though it enters the textual tradition of the vitae via an adapted portion of De Genesi contra Manichaeos in Bede’s metrical Vita Sancti Cuthberti (VCM). Both Augustine and Bede argue, with slight differences, that fallen Creation can be restored into prelapsarian harmony with humanity by way of sanctity. Each individual vita engages with this understanding of the Fall in distinct, though ultimately interrelated, ways, and the chapters of this thesis will therefore explore each text individually. Chapter 1 argues that the anonymous Vita Sancti Cuthberti (VCA) unites Cuthbert’s ability to restore Creation with the theme of monastic obedience, linking the ordering of a monastery to the restoration of prelapsarian harmony. The VCA also seeks to create sites for potential lay pilgrimage in the landscapes of Farne and Lindisfarne by highlighting the present efficacy of Cuthbert’s miracles. Chapter 2 argues that Bede’s VCM not only reveals his early attempt to fashion Cuthbert into the primary saint for Britain, via a focus on Cuthbert's obedience to the Divine Office, but also that the restoration of Creation functions as a ruminative tool. Chapter 3 argues that Bede transforms the nature of Cuthbert’s sanctity in his prose Vita Sancti Cuthberti (VCP) from static to developmental, influenced by the Evagrian Vita Antonii, and that Creation is adapted to function as the impetus for, and evidence of, Cuthbert’s progression. Chapter 4 argues that Felix's Vita Sancti Guthlaci (VSG) unites the development of Guthlac with a physically delineated Creation, and that the restoration of Creation is elevated to an even greater degree here than in Bede's hagiography. Chapter 5 argues that the author of the Old English Prose Guthlac (OEPG) grounds his vita by utilizing a landscape lexis shared with contemporary boundary clauses, so that here the relationship between the saint and Creation has greater force; it further argues that Guthlac A uniquely connects Guthlac with the doctrine of replacement, consolidating links between his arrival to the eremitic space and the restoration of prelapsarian Eden.